Mother’s knowledge and attitude regarding febrile convultion in children - Paudel, Binita; Rana, Gayatri; Lopchan, Milan (Journal of Chitwan Medical College, 2018)
Febrile convulsion is the most common seizure in children worldwide. Between 1 and 4% of children develop febrile convulsion within in 5 years of life. The study aimed at finding out mothers’ knowledge and attitude regarding febrile convulsion in children. A descriptive cross sectional research design was used in which 126 mothers mother of children who are from 6 month to 5 years attending pediatric OPD of Chitwan Medical College- teaching hospital, Bharatpur- 10, Chitwan were interviewed by using semi-structured interview schedule. Data was analyzed by using IBM SPSS version 20. The study showed that, 29.4% respondents were having high knowledge regarding febrile convulsion in children, 53.2 % respondents having medium and 17.5% respondents having low knowledge regarding febrile convulsion in children. There was significant low knowledge regarding predisposing factors of febrile convulsion than other factors of febrile convulsion among respondents. There was no association between demographic variables and knowledge level of mothers on febrile convulsion. None of the respondents were having unfavorable attitude regarding febrile convulsion in children, 25.4% mothers having favorable attitude and 74.6% mothers having neutral attitude towards febrile convulsion in children. The study also reveals that there was significance association between ages of mother (0.000) and number of children (0.009) and attitude regarding febrile convulsion in children. There was positive correlation between knowledge and attitude of mothers regarding febrile convulsion in children.